Tinjauan Yuridis terhadap Pembelaan Terpaksa (Noodweer) sebagai Alasan Penghapus Pidana - lda Ayu Mirah Widnyani; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Warmadewa Press, 2020)
Defending oneâ€™s self in a forced state, or in the Criminal Code known as â€œforced defenseâ€ (Noodweer), arose as a result of a situation where a victim of an act of crime was in a coercive situation or state so as to be forced to carry out self-defense. A person becoming a victim of a crime has the space to make use of power and efforts to defend and save his/her possessions, honor, and soul. This research highlights two issues related to this. First, which type of crime is included in forced defense? Second, what is the legal basis for the elimination of criminal acts against a person doing self-defense in a coercive state in a crime? To uncover these issues, this research was conducted using the design and method of normative legal research with statutory and conceptual approaches. The results show that the concept contained in Article 49 Paragraph 1, interpreted as a noodweer, aims to protect oneself and others, the honor of oneâ€™s own morality or property, which when compared to the criminal acts of robbery referred to as being clearly considered the noodweer. ln addition, the legal basis for the elimination of criminality against the act of noodweer is the legal conclusion resulted from the facts revealed at the trial and the values to uphold, that is, to appraise and understand the sense of justice living in the community according to the judgeâ€™s point of view. Based on this fact, noodweer and the basis for the elimination of criminal acts against self-defense if compared to related cases have been considered as noodweer in accordance with Article 49 Paragraph 1. Further research is expected to further broaden the scope or coverage of research on the self-defense.